A KINETIC MODEL OF ISOTOPIC EXCHANGE IN DISSOLUTION-PRECIPITATION PROCESSES - Dubinina E.O.; Lakshtanov L.Z. (My University, 1997)
A model is derived for the isotopic fractionation between a mineral and a fluid phase in three dissolution-precipitation processes: the transformation of an unstable mineral into a stable one, and mineral-fluid mass transfer with partial or complete dissolution of the starting mineral. It is assumed that (1) the isotopic fractionation factor between the freshly formed portion of the mineral and the fluid is constant (not necessarily equilibrium) and (2) isotopic exchange before the dissolution and after precipitation is negligible. The model takes into account the possible variation in composition of the precipitating solid. Early formed solids are regarded as isolated from the system.The evolution of isotopic compositions of fluid, freshly formed mineral and bulk solid are considered. Mineral synthesis, Ostwald ripening, and repeated recrystallization are described as the examples of different types of dissolution-precipitation processes. To illustrate the model, numerical calculations of isotopic compositions and the fraction of isotopic exchange (F) for the system silica gel-quartz-water at 500°C are performed.The F value depends on the mass of the mineral transferred through the fluid and the mineral/fluid ratio for all the processes considered. The first type of dissolution-precipitation process is characterized by the F variation from zero up to values above unity. In the case of repeated dissolution-precipitation process, F shows an oscillatory character, as opposed to a diffusive model of isotopic exchange. During Ostwald ripening, F strongly depends on the crystal size distribution of the initial sample.